THE INFLUENCE OF THE DISCOVERY LEARNING MODEL ON LEARNING OUTCOMES IN HISTORY SUBJECTS - M. Rasyid Ridho; Wahidul Basri (Sean Institute, 2023)
The learning model has a great influence on student learning outcomes. Therefore the purpose of this research is to determine the effect of the Discovery Learning model on student learning outcomes in History subjects. The subjects of this study were 72 students of class XI IPA 1 and XI IPA 2 SMA Negeri 1 Lembah Melintang, West Sumatra, Indonesia. This quasi-experimental study uses a control class and an experimental class. The control class uses a conventional learning model and the experimental class uses the Discovery Learning learning model. This study uses quantitative and primary data types. Data were obtained using test instruments through the implementation of pre-test and post-test. The data is calculated using the Independent Sample T-Test to measure the effect of applying the Discovery Learning model. In using the Independent Sample T-Test test, the requirements for the normality test, homogeneity test, and t-test are used. The results of the research on the implementation of the pre-test for the control class obtained a value of 54.67 and for the experimental class 50.14. The implementation of the post-test for the control class obtained a value of 84.61 and 89.83 for the experimental class. The results of the normality and homogeneity tests obtain a value above 0.05 which interprets that the data used is normal and homogeneous. In the independent sample t-test, the value of Sig. (2-Tailed) which is 0.000. This interprets that the Discovery Learning learning model has a good influence on student learning outcomes in History subjects. So that the Discovery Learning learning model is recommended for learning History.